Students' mathematical reasoning abilities are viewed from Van Hiele’s theory - Arshifa, Luthfiyana Dian; Setyaningsih, Rini (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mathematical reasoning is the ability of a person's brain that includes the presentation of statements, making conjectures, performing mathematical manipulations, and presenting conclusions. This study aims to analyze or describe the ability of mathematical reasoning in solving trigonometric problems based on Van Hiele's level of thinking among high school students. This research uses a descriptive qualitative method. Data collection techniques consist of tests and interviews. Data analysis involves data presentation, reduction, and conclusion. The results of this study show that students at level 0 (visualization) of Van Hiele's level of thinking have one indicator of mathematical reasoning ability, which is to present statements. Students at level 1 (analysis) of Van Hiele's level of thinking have two indicators of mathematical reasoning: presenting statements and making conjectures. Students at level 2 (informal cut) of Van Hiele's level of thinking have three indicators of mathematical reasoning: presenting statements, making conjectures, and mathematical manipulations. Students at level 3 (deduction) of Van Hiele's level of thinking have four indicators of mathematical reasoning ability: presenting statements, making conjectures, mathematical manipulations, and drawing conclusions. Therefore, the higher the thinking level of the students at Van Hiele, the higher their mathematical reasoning ability. Whereas, the lower the Van Hiele thinking level of students, the lower their mathematical reasoning ability.